Relationship Pattern of Pedagogic Competence with Moderating Structural Equation Modeling Score Factor (MSEM-SF) - Moch Bisyri Effendi; Agus Samekto; Emma Julianti (Journal of Economics, Business, and Accountancy Ventura, 2017)
The quality of education depends highly Â on the capacity of educational units in transforming the learners to gain added value, whether it is related to the aspects of thinking, taste, heart, and body. Among the components of education, teachers and lecturers are very important and strategic factors in an effort to improve the quality of education in every educational unit. The purpose of this research is to know the effect of professional competence, social competence on pedagogic competence with personality competence as moderation variable based on studentsâ€™ perception. The analytical method used is Confirmatory Factor Analysis (CFA) to confirm the validity and reliability of the indicator of the latent variables and Moderating Structural Equation Modeling Score Factor (MSEM-SF) to determine the effect of moderation. The results show that personality competence moderates the relationship of the effect of professional competence on pedagogic competence but personality competence does not moderate relationship of the effect of social competence on pedagogic competence. This implies that, a good professional competence can accelerate the improvement of pedagogic competence quality supported by good personality competence.